(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Vehicle to Grid (V2G) technology is becoming a promising application for Electric Vehicles (EVs) in modern grids. This manuscript describes the potential benefits of V2G, its functions, the scheme of V2G and demonstrates its applicability on a microgrid. We explain how EVs can act as a spinning reserve to store excess grid power in the vehicle batteries and feed the power back to the grid if the demand arises. This helps to regulate the grid’s frequency within its nominal ratings. We demonstrate this on a microgrid system with a fleet of EVs connected with solar, wind, and a Diesel generator.